The Two-Component Locus MSMEG_0244/0246 Together With MSMEG_0243 Affects Biofilm Assembly in M. smegmatis Correlating With Changes in Phosphatidylinositol Mannosides Acylation - Li, Miaomaio; Gašparovič, Henrich; Weng, Xing; Chen, Si; Korduláková, Jana; Jessen-Trefzer, Claudia (Frontiers in Microbiology, 2020)
Ferric and ferrous iron is an essential transition metal for growth of many bacterial species including mycobacteria. The genomic region msmeg_0234 to msmeg_0252 from Mycobacterium smegmatis is putatively involved in iron/heme metabolism. We investigate the genes encoding the presumed two component system MSMEG_0244/MSMEG_0246, the neighboring gene msmeg_0243 and their involvement in this process. We show that purified MSMEG_0243 indeed is a heme binding protein. Deletion of msmeg_0243/msmeg_0244/msmeg_0246 in Mycobacterium smegmatis leads to a defect in biofilm formation and colony growth on solid agar, however, this phenotype is independent of the supplied iron source. Further, analysis of the corresponding mutant and its lipids reveals that changes in morphology and biofilm formation correlate with altered acylation patterns of phosphatidylinositol mannosides (PIMs). We provide the first evidence that msmeg_0244/msmeg_0246 work in concert in cellular lipid homeostasis, especially in the maintenance of PIMs, with the heme-binding protein MSMEG_0243 as potential partner.